2020
DOI: 10.1111/pce.13897
|View full text |Cite
|
Sign up to set email alerts
|

Indole primes defence signalling and increases herbivore resistance in tea plants

Abstract: Upon herbivore attack, plants emit herbivore-induced plant volatiles (HIPVs). HIPVs can prime defences and resistance of intact plants. However, how HIPVs are decoded and translated into functional defence responses is not well understood, especially in long-lived woody plants. Here, we investigated the impact of the aromatic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 69 publications
2
66
0
Order By: Relevance
“…Ca 2+ is an important messenger molecule in signal transduction, and widely participates in plant physiological and biochemical processes 32, 36, 76 . It has previously been shown that Ca 2+ application protects plants against environmental stress, including cold injury and salt stress 77, 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ is an important messenger molecule in signal transduction, and widely participates in plant physiological and biochemical processes 32, 36, 76 . It has previously been shown that Ca 2+ application protects plants against environmental stress, including cold injury and salt stress 77, 78 .…”
Section: Discussionmentioning
confidence: 99%
“…The second major theme is the role of volatile signals in plant–plant communication, particularly in the context of defence against pathogens and herbivores. Frank et al (2021) demonstrate the potential importance of isoprene and β‐caryophyllene emissions in resistance priming against pathogens, while two papers show how indole (Ye et al, 2020) and 4,8‐dimethyl‐1,3,7‐nonatriene (DMNT) (Jing et al, 2020) emissions in tea plants lead to herbivore resistance. Finally, Moreira et al (2020) provide evidence that fungal pathogens may suppress volatile emissions in potato, to negate resistance priming in neighbouring plants.…”
mentioning
confidence: 99%
“…For instance, most CsLACs contained hormone-related elements, including JA and SA signaling elements (Figure 4). JA and SA pathways are thought to play key roles in plant-induced defense responses to biotic and abiotic stresses [36][37][38][39]. Likewise, JA signaling was well-established as the core pathway that regulated tea plant defense against herbivores [24].…”
Section: Discussionmentioning
confidence: 99%